Shifting sands of marine eutrophication assessments: building a future approach for UK marine waters - Devlin, Michelle J.; Graves, Carolyn A.; Greenwood, Naomi; Allerton, Mollie; Bresnan, Eileen; Holland, Matthew M.; McQuatters-Gollop, Abigail; Tett, Paul; Tracey, Dieter; Best, Mike (Frontiers in Ocean Sustainability, 2025)
The assessment of water quality, and in particular, of eutrophication, has been a core activity to establish, disseminate, and communicate the impact of anthropogenic influences on coastal and marine waters in the United Kingdom (UK) and globally. To date, the UK assessments of eutrophication have focused heavily on indicators, either singularly or in combination, associated with a numerical threshold, with supporting science concentrating on defining relevant thresholds and relating exceedances to management actions. However, as our understanding of the complexity of estuarine and coastal zone processes in terms of variability, time lags, ecological interactions and climate resilience has evolved, so too must the structure of our water quality assessments. This paper presents a review of existing UK eutrophication assessments, identifying what has worked and where gaps still exist, particularly as our ecosystems face rapid changes. From the gap analysis, we present a series of recommendations for future eutrophication assessments, assessing the feasibility of implementing those recommendations through consideration of effort, complexity and costs. This work presents a set of headline activities offering a renewed and revised approach to the structure of UK eutrophication assessments that will progress complex data flows, achieve enhanced alignment between directives, embed new indicators, greater understanding of ecosystem impacts and consideration of the shifting climate baseline.